Pengaruh Profitabilitas, Likuiditas dan Solvabilitas Terhadap Nilai Perusahaan Pada Perusahaan Perbankan - Jamiah Jamiah; Rizali Hadi (Universitas Lambung Mangkurat, 2023)
This study aims to determine the effect of profitability, liquidity and solvency partially and simultaneously on firm value in banking companies listed on the Indonesia Stock Exchange in 2014-2018. This study uses a quantitative approach with descriptive research type. The sample of this research is 19 companies that have met the criteria that have been set, the sampling method uses non-probability sampling with purposive sampling technique and data calculations using SPSS v.26.This study provides an illustration that the distribution of data that is used as a reference in the study is indicated not to be properly distributed, because in the recapitulation of the financial annual report there are several companies that do not present complete financial statement items, this affects the analysis of the processed data,The results showed that partially the profitability variable had no effect on firm value, liquidity had no effect on firm value, while partially solvency had a negative effect, and simultaneously the profitability, liquidity and solvency variables had no effect on firm value. Keywords: Profitability ; Liquidity ; Solvency ; The value of the company ; Banking